ANALISIS IMPLEMENTASI KEBIJAKAN RETRIBUSI KEBERSIHAN DAN KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH KOTA PALU - Widodo, Arwan (Katalogis, 2018)
The purpose of study are: to determine and analysis the implementation of cleaning retributions policy and its contributions on local revenue of Palu City, to determine and anaalyze supporting and inhibitng factors toward the implementation of cleaning retribution policy to increase the local revenues. The study of descriptive qualitative. The result conclude that:cleaning retribution in Palu City as one of the sources of local revenues is organized under the coordination of Departemen of Cleaning and Landscaping of Palu City. Retribution withdrawal should be followed by better cleaning service. Factor supporting the implementation of cleaning retribution in Palu City includes: commitment of the decition makers and implementers, authority in the selection and formulation of waste managemenr policy, recousces support, cooperation between The departemen of Cleaning and Landscaping with Integrated Licencing Agency of Palu in cleaning retribution withdrawal. Inhibiting factor include low quality of recourses, low of education and commiment and tenacity in performing the task, insufficient facilities and infrastrukture, both quality and quantities, the increased volume of waste, the demand of the community toward the improvement cleaning services, and the absence of waste recycling technology. In addition, ineffective sanctions againt the offender of the abusive littering, the lateness of the waste transport, and minimal operational cost also hinder the implementation of cleaning retribution policy in Palu City.